Fostering Young Entrepreneurs: Family Support as the Cornerstone of Intentions - Siregar, Onan Marakali; Mardhiyah, Ainun; Nasution, Muhammad Dharma Tuah Putra; Maulidina, Maulidina (International Review of Management and Marketing, 2024)
The present study investigates the influences of perceived family support (PFS), perceived desirability (PD), and perceived feasibility (PF) on entrepreneurial intentions (INT) among youth in both urban and rural settings. Grounded in the Entrepreneurial Event Model (EEM), this research highlights the complex interplay between individual and social factors that shape entrepreneurial aspirations. The EEM underscores the critical roles of PD and PF in predicting entrepreneurial intentions alongside the propensity to act. A quantitative research methodology was employed, utilizing a cross-sectional survey design with a diverse sample of 291 youth aged 16-24 years, including university students from both urban and rural areas. Data were collected through paper-based surveys distributed across educational institutions and community centers. The results reveal significant direct effects of PD (β = 0.318) and PF (β = 0.380) on INT, confirming the importance of cognitive factors in entrepreneurial decision-making. Furthermore, PFS positively influences both PD (β = 0.334) and PF (β = 0.469), highlighting the multidimensional role of family support. Notably, both PF and PD serve as mediators in the relationship between PFS and INT, underscoring the critical role of family dynamics in shaping the entrepreneurial aspirations of young individuals. This study contributes to the EEM by reaffirming PD and PF as crucial predictors of INT while illustrating how PFS enhances these perceptions. The findings emphasize the importance of family involvement in nurturing entrepreneurial intentions, suggesting that targeted programs to engage family support could strengthen the entrepreneurial ecosystem. Additionally, this research prompts future investigations into other external factors influencing perceived desirability and feasibility, thereby broadening the applicability of the EEM across diverse contexts.